Law, Social Policy, and the Constitution of Markets and Profit Making - Veitch, Kenneth (Journal of Law and Society, 2013)
This article explores the relationship between law, society, and economy in the context of the contemporary British welfare state. Drawing on themes in Polanyi's The Great Transformation, it identifies the constitutive role of contemporary social policy and law in the creation and maintenance of markets and opportunities for the private sector in the field of welfare, focusing on the institutional mechanisms being put in place to encourage this. What emerges is a reformulation of the function of the welfare state and related law, as these are no longer predominantly driven by a logic of social protection via redistribution to those in need, but increasingly reflect the state's desire to create openings for the private sector within welfare. The institutions that once contributed to ensuring the embeddedness of the market economy in society now play an important role in processes of disembedding – with potentially detrimental consequences for those seeking assistance from the welfare state.
Law; Sociology
Keywords: Great Britain; disembeddedness; welfare state